Inclusive culture in pre-school institutions - Novachevska, Irena; Dimchevska, Ilinka; Pavlovska, Sashka; Chichevska Jovanova, Natasha; Dimitrova Radojichikj, Daniela (Faculty of Philosophy, Skopje, 2011)
Inclusive education is a rational concept that refers to the overall and long-term transformation of institutional systems in society, especially in education. Along with the transformation, a number of important and unresolved issues still appear in both theory and practice, as the duty of preschool institutions and schools is to educate every student in the mainstream education system. One of the most important aspects of inclusion is the inclusive culture. Regardless of the good inclusive policy and practice, one cannot talk about successful inclusion without a properly developed inclusive institutional culture. This paper is a contribution to the research considering the development of inclusive culture in three preschool institutions. It is based on the thinking and attitudes of the preschool staff toward the necessity of developing and nurturing an inclusive culture. Successful inclusion of pupils with special needs in the mainstream school system cannot be conceived without an inclusive culture.
Инклузивната култура во предучилишните установи
Keywords: inclusive education, inclusive culture, preschool institutions.